Extensive Aortic Thromboembolism in a Patient With Erdheim-Chester Disease: A Case Report - He, Jiangping; Fang, Xin; Zhang, Xianfeng; Chen, Kuang; Huang, Jiao (Frontiers in Cardiovascular Medicine, 2022)
Background Erdheim-Chester disease (ECD) is a rare disease that affects multiple systems and is characterized by non-Langerhans cell histiocytosis. Classic clinical signs include long bone infiltration, central nervous system involvement, diabetes insipidus, and sheathing of the entire aorta. However, thrombosis is not recognized as a typical cardiac manifestation of ECD. Here, we report the case of an ECD patient with extensive arterial thrombus formation and embolism in several sections of the aorta. Case A 36-year-old woman was admitted due to recurrent fever and left finger cyanosis for 20 days. Laboratory tests revealed that her C-reactive protein and interleukin-6 levels were significantly elevated. Thoracic computed tomographic angiography (CTA) revealed thrombosis from the aortic arch to the left subclavian artery accompanied by severe stenosis of the left subclavian artery. Abdominal CTA revealed splenic infarction due to splenic artery embolism and thrombus formation in multiple abdominal arteries. She underwent emergent arterial thrombectomy. During hospitalization, she complained of polyuria. The desmopressin test and pituitary magnetic resonance imaging findings suggested diabetes insipidus. Furthermore, positron emission tomography-computed tomography and bone emission computed tomography showed long bone impairment, and pathological examination of the bone samples confirmed ECD. Steroids and tocilizumab were selected as the initial therapies; however, thrombosis continued to develop. After replacement of tocilizumab with interferon-α, her condition became stable. Conclusion Although extremely rare, fatal thrombosis may be a significant cardiovascular manifestation of ECD.